Household-based critical influence factors of biogas generation technology utilization: A case of Punjab province of Pakistan - Jabeen, Gul; Yan, Qingyou; Ahmad, Munir; Fatima, Nousheen; Jabeen, Maria; Li, Heng; Qamar, Shoaib (Renewable energy, 2020)
This research comprehensively examined the contributions of households’ critical influence factors (CRIFs) in BGT utilization. The data based on a sample of 695 households from seven selected districts of Punjab province of Pakistan. The empirical findings are: first, among the households’ preference based CRIFs, cooking as a utilization mode imparted positive and significant influence on BGT utilization. It implicated that cooking was found to be the dominant preference of households to utilize the BGT. Moreover, the health risk factor was exposed to be important in BGT utilization. This is likely for people to attach importance to their health. Second, dual nature of the influence of gender is observed: (i) it emphasized the role of woman empowerment in choice of BGT, and also, (ii) as the females need to spend extra time in fuel collection, they want to switch to BGT. Third, concerning the socio-economic and infrastructural influence factors, the education of both household head and chef portrayed a positive influence on BGT utilization. Moreover, households with relatively more land ownership and livestock were more probable to utilize BGT. Finally, the users of the BGT experienced the financial, health, environmental protection, and crop harvest benefits as compared to non-users of BGT. •Examined households-based critical influence factors of biogas generation technology (BGT) utilization.•A propensity score matching technique has been adopted for influence assessment.•Found significant positive contributions of households’ preference-based influence factors.•Identified contributions of socioeconomic and infrastructural influence factors.•Cooking as a utilization mode and health risk factor exposed positive impact on BGT utilization.